The responsibility to protect: ending mass atrocity crimes once and for all - Evans, Gareth J. (Brookings Institution Press, 2008)
The problem : the recurring nightmare of mass atrocities -- The solution : from "the right to intervene" to "the responsibility to protect" -- The scope and limits of the responsibility to protect -- Before the crisis : the responsibility to prevent -- During the crisis : the responsibility to react -- Responding to crises : when is it right to fight? -- After the crisis : the responsibility to rebuild -- Institutional preparedness : the actors